2021
DOI: 10.3390/su13052482
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Retail Settings: A Sustainable and Adaptive Strategy for City Centre Stores

Abstract: The fact that an already damaged retail industry is being challenged by a pandemic makes the industry’s survival a matter of urban resilience. Sustainable and adaptive strategies are needed to reverse the negative development of the retail sector, and in this conceptual paper, a new perspective is suggested based on episodic retail settings. Such a perspective can increase a physical store’s attraction and may serve as a flexible operation strategy for urban retailers and give added value to urban consumers as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Various customer groups exhibited diverse behavioral changes. Some began frequenting larger stores due to their ability to facilitate social distancing, while, others conversely shifted their shopping preferences away from larger retailers, opting instead for smaller stores, local retail centers, and out-of-town shopping alternatives [57][58][59]. Eger et al (2021) observed that consumers from various generations are likely to exhibit distinct changes in their consumption patterns when confronted with significant societal events [41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various customer groups exhibited diverse behavioral changes. Some began frequenting larger stores due to their ability to facilitate social distancing, while, others conversely shifted their shopping preferences away from larger retailers, opting instead for smaller stores, local retail centers, and out-of-town shopping alternatives [57][58][59]. Eger et al (2021) observed that consumers from various generations are likely to exhibit distinct changes in their consumption patterns when confronted with significant societal events [41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…personal risk appraisals) ( Wang et al, 2022 ). In many places, consumers altered the location of where they chose to shop, tending to avoid larger retailers and crowded high street centres ( Lashgari & Shahab, 2022 ) in favour of smaller stores ( Li et al, 2020 ), local retail centres ( Ballantyne et al, 2022 ) and out-of-town based shopping alternatives ( Sundström et al, 2021 ). A study using mobile phone records for retail foot traffic in busy commuter zones in the US found a significant fall in consumer traffic even before legal restrictions were enacted ( Goolsbee & Syverson, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These aspects also influence various RF management processes, for instance, product allocation is closely related to shelve-restocking activities, product visibility affects customer services, and aisle accessibility facilitates maintenance (Calingo, 2018; Tarigan et al , 2018). In fact, studies imply that the existence of traditional RF facilities, with the emergence of the newly trending online retail stores, may depend mainly on optimizing these costumer experiences (Edirisinghe and Munson, 2023), especially with the reported decline in fixed-store settings (Sundström et al , 2021). Despite this, designers base decisions on intuition rather than informed spatial analysis (Marciniak, 2021; Sanz et al , 2018), resulting in little integration between design concepts and costumer perspectives.…”
Section: Introductionmentioning
confidence: 99%